Cast Stone Formulation for Nuclear Waste Immobilization at Higher Sodium Concentrations. Issue 6 (14th November 2014) - Fox, Kevin; Cozzi, Alex; Roberts, Kimberly; Edwards, Thomas
Abstract : Low activity radioactive waste at U.S. Department of Energy sites can be immobilized for permanent disposal using cementitious waste forms. This study evaluated waste forms produced with simulated wastes at concentrations up to twice that of currently operating processes. The simulated materials were evaluated for their fresh properties, which determine processability, and cured properties, which determine waste form performance. The results show potential for greatly reducing the volume of material. Fresh properties were sufficient to allow for processing via current practices. Cured properties such as compressive strength meet disposal requirements. Leachability indices provide an indication of expected long‐term performance.